Diagnosis of degradation of the Santa Bárbara River in the urban area of the municipality of São Gonçalo do Rio Abaixo (MG) (Research, Society and Development, 2019)
In the course of history, the emergence of cities is linked to the proximity of a water course. In this context, the municipality of São Gonçalo do Rio Abaixo (MG), is located and developed on the banks of the Santa Bárbara river. Thus, this work aimed at the elaboration of the diagnosis of degradation of a stretch of 5.35km of this river and to propose of measures aimed at its restoration. For this, field research was used to observe the fluvial and environmental conditions, such as morphology and habitat diversity; in addition to the analysis of documents related to water quality and satellite images obtained in the years 2007 to 2017 to evaluate the use of the soil in the analyzed section. Considering the analysis of the satellite images, it was noticed the expansion of the urbanized area and the suppression of the vegetation in some stretches of the Santa Bárbara River. In addition, a degradation considered "average" for the analyzed section was verified, since the water course, although it is in natural bed, receives in natura effluents. Regarding the proposed restoration techniques, since there is locally silting and sliding of the margins, live cuttings and biomantas can be used to control these. Finally, a continuous preservation of the water course is necessary, so that, in addition to adequate techniques to mitigate the negative environmental impacts identified, the actions to be implemented should involve the awareness and participation of the local population.